MANIPULATION AND CONTROL OF CONSCIOUSNESS AS BASIC MECHANISMS OF INFLUENCE ON ADHERENTS OF UNTRADITIONAL RELIGIOUS ASSOCIATIONS - Богдановський, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article description of such mechanisms of socially psychological influence is given on consciousness of adherents of untraditional religious associations (NRA) as manipulation and cult control of consciousness.